VD_FINDINFO PP 30/09 - 18/2010 vom 9. April 2010 - VD Tribunal cantonal (2010)
PRESTATION DE PRÉVOYANCE, SURASSURANCE | 34a LPP, 73 LPP, 24 al. 2 OPP2, 24 OPP2, 109 LPA-VD, 117 al. 1 LPA-VD, 55 LPA-VD, 94 al. 1 let. a LPA-VD